KEMITRAAN PERPUSTAKAAN DAN INDUSTRI: STUDI Dl PERPUSTAKAAN TAMAN GASIBU BANDUNG SEBAGAI CSR BANK BJB - Neneng Komariah (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
Literacy movement should be supported by the availability of qualified and accessible reading materials for those who are interested in reading. Public libraries can support literacy campaign, therefore it is necessary to strengthen the public libraries.  The government of West Java Province built Taman Gasibu Bandung Library located on the side of the sports field of Gasibu as a result of the partnership with Bank of BJB. This study aimed to determine the process and model of partnership between the provincial government of West Java I Dispusipda with BJB in building Taman Gasibu Library. This study used qualitative methods with the techniques of data collection by interviews, focus group discussions and study of literature. The results showed that the partnership process in building Taman Gasibu Library was that the provincial government of West Java provided place while BJB provided funds for the onstruction of the building, the purchase of book collections and the provision of computers and furniture. The partnership model started by the direct communication of the Governor of West Java with BJB, then the technical things were handled by Dispusipda that did regular consultation with BJB. After the library was handed over, the management of the library is fully handled by Dispusipda without any involvement of BJB.